Human supplementation with Pediococcus acidilactici GR-1 decreases heavy metals levels through modifying the gut microbiota and metabolome - Pengya Feng; Jinfeng Yang; Shuai Zhao; Zhenmin Ling; Rong Han; Ying Wu; Ei-Sayed Salama; Apurva Kakade; Aman Khan; Weilin Jin; Weibing Zhang; Byong-Hun Jeon; et al. (npj Biofilms and Microbiomes, 2022)
Abstract Exposure to heavy metals (HMs) is a threat to human health. Although probiotics can detoxify HMs in animals, their effectiveness and mechanism of action in humans have not been studied well. Therefore, we conducted this randomized, double-blind, controlled trial on 152 occupational workers from the metal industry, an at-risk human population, to explore the effectiveness of probiotic yogurt in reducing HM levels. Participants were randomly assigned to two groups: one consumed probiotic yogurt containing the HM-resistant strain Pediococcus acidilactici GR-1 and the other consumed conventional yogurt for 12 weeks. Analysis of metal contents in the blood revealed that the consumption of probiotic yogurt resulted in a higher and faster decrease in copper (34.45%) and nickel (38.34%) levels in the blood than the consumption of conventional yogurt (16.41% and 27.57%, respectively). Metagenomic and metabolomic studies identified a close correlation between gut microbiota (GM) and host metabolism. Significantly enriched members of Blautia and Bifidobacterium correlated positively with the antioxidant capacities of GM and host. Further murine experiments confirmed the essential role of GM and protective effect of GR-1 on the antioxidative role of the intestine against copper. Thus, the use of probiotic yogurt may be an effective and affordable approach for combating toxic metal exposure through the protection of indigenous GM in humans. ClinicalTrials.gov identifier: ChiCTR2100053222